PENERAPAN PENUGASAN KELOMPOK UNTUK MENINGKATKAN KERJA SAMA MAHASISWA D1 PAJAK POLITEKNIK KEUANGAN NEGARA STAN BALAI DIKLAT KEUANGAN MEDAN - Susilo, Budi (Polytechnic of State Finance STAN, 2016)
Synergy is one of the values of the Ministry of Finance that should be internalized by students of PKN-STAN. Cooperation is the key element in creating synergies. Based on the author's observation, collaboration levels of college students in Diploma Program I of Tax still need to be improved. Students tend to learn individually rather than in a group, so the collaboration is not formed as a team. It needs a great effort from the lecturers to improve student collaboration during lectures, so that students learn from each other and cooperate in solving various problems of learning. The main purpose of this research is to improve cooperation among students using work-in-group learning methods in the Capita Selecta Personality Development subject.The method used is Classroom Action Research using three cycles. The subjects of the research are three classes at the Diploma I Tax Program in the first semester on Regional Finance Education and Training Office of Medan. The research design is that every class was classified into five groups with each group consists of five to six students. During the learning process, author made observations about this collaboration. The observation results of each cycle is used as a reaction for the next cycle that can be used to enhance the cooperation of college students in accordance with the set targets. Data were analyzed descriptively and quantitatively. The results showed that the collaboration of college students increased during the lecture by applying team work learning methods. In the first cycle, the average of student collaboration is 2.69, showing lack of cooperation among students, in second cycle the result score is 4.13, which means they are able to work together, and in third cycle is 4.15 which means able to cooperate.